1988
DOI: 10.1192/bjp.153.4.460
|View full text |Cite
|
Sign up to set email alerts
|

Physiogenesis and Psychogenesis in the ‘Post-Concussional Syndrome’

Abstract: The aetiological factors relevant to the development of post-concussional symptoms are reviewed. From the numerous studies carried out to date, it would appear that both physiogenic and psychogenic influences are important in their genesis. However, where mild-to-moderate injuries are concerned, organic factors are chiefly relevant in the earlier stages, whereas long-continued symptoms are perpetuated by secondary neurotic developments, often of a complex nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
151
0
5

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(159 citation statements)
references
References 34 publications
3
151
0
5
Order By: Relevance
“…This raises the additional possibility that the deficits found in the mild TBI group may partially or completely resolve over time. Indeed, this may explain why studies often report a higher frequency of problems in the early stages after a mild TBI than in the later stages (Kibby & Long, 1996;Lishman, 1988;Van der Naalt et al, 1999). It remains to be seen whether measures designed to target the effects of diffuse damage are better able to predict which mild TBI patients will experience long-term residual problems than traditional neuropsychological tests.…”
Section: Discussionmentioning
confidence: 95%
“…This raises the additional possibility that the deficits found in the mild TBI group may partially or completely resolve over time. Indeed, this may explain why studies often report a higher frequency of problems in the early stages after a mild TBI than in the later stages (Kibby & Long, 1996;Lishman, 1988;Van der Naalt et al, 1999). It remains to be seen whether measures designed to target the effects of diffuse damage are better able to predict which mild TBI patients will experience long-term residual problems than traditional neuropsychological tests.…”
Section: Discussionmentioning
confidence: 95%
“…The strict rest group may have been better able to articulate their symptoms because they were slightly older. Lishman et al (1988) suggested that physiologic and psychological factors both contribute to the development of postconcussive syndrome, with psychological factors contributing more to symptoms over time. 42 The deleterious effects of strict rest may have more to do with emotional distress caused by school and activity restriction.…”
Section: Figurementioning
confidence: 99%
“…Lishman et al (1988) suggested that physiologic and psychological factors both contribute to the development of postconcussive syndrome, with psychological factors contributing more to symptoms over time. 42 The deleterious effects of strict rest may have more to do with emotional distress caused by school and activity restriction. Missing social interactions and falling behind academically may contribute to situational depression increasing physical and emotional symptoms.…”
Section: Figurementioning
confidence: 99%
“…A minority of individuals develop postconcussion syndrome (PCS), a persistent constellation of symptoms that may include headache, dizziness, fatigue, sleep disturbance, sensitivity to light and noise, anxiety, depression, and complaints of concentration and memory problems that may or may not be verified by cognitive testing [17,[66][67]. The causes of PCS are controversial and may involve an interplay between the neurological injury and psychological factors [68][69]. Weight has summarized the difficulties associated with assessing PCS [70].…”
Section: Postconcussion Syndromementioning
confidence: 99%